A constrastive case study of orthodox and alternate adult literacy initiatives, as regards their assumptions about literacy, pedagogy, and curriculum - Fine, Zelma (Centre for Applied Language and Literacy Studies and Services in Africa, 2015)
Includes bibliographical references (p. 83-89).